Synthesis of MCF-supported AuCo nanoparticle catalysts and the catalytic performance for the CO oxidation reaction. Issue 121 (23rd November 2015) - Li, Lin; Chai, Song-Hai; Binder, Andrew; Brown, Suree; Yang, Shi-Ze; Dai, Sheng
Abstract : AuCo/MCF calcined at 500 °C for 1 h was found to produce the most active and stable catalyst for CO oxidation. In situ FTIR results of AuCo/MCF catalysts with different treatments. Abstract : The oxidation of carbon monoxide under low temperature is increasingly becoming an important process, and supported gold nanoparticles have generated an immense interest in this field due to their extremely high reactivity. In this paper, we have synthesized MCF-supported AuCo nanoparticles, and through heating the AuCo/MCF in an O2 atmosphere, we have developed Au–CoO x heterostructured catalysts for CO oxidation. The structure of the Au–CoO x /MCF hybrid catalysts was investigated by using a combination of XRD, TEM, HR-TEM, EDX, SEM, XPS and in situ FTIR experiments. Various pretreatment conditions were required to form a highly active and stable Au–CoO x /MCF catalyst to achieve 100% CO conversion under low temperature. The AuCo/MCF catalyst calcined at 500 °C for 1 h was found to produce the most active and stable catalyst for CO oxidation with the highest activity at a reaction temperature of 30 °C for 15 h on-stream. Furthermore, XRD results of the used Au–CoO x /MCF catalyst showed its good resistance to sintering during catalytic process. However, by heating the Au–CoO x /MCF catalyst in H2 at 400 °C for 1 h to reduce the CoO x back to Co to reform the AuCo catalyst, it was found that the AuCo/MCF catalyst was much less active for CO oxidation. This was explained by the in situ FTIR results, which showed that CO molecules could be chemisorbed and activated on the Au–CoO x /MCF catalyst more than on the AuCo/MCF catalyst. It was likely that the increased interfacial contact between the Au and CoO x formed the most active site on the catalyst and was responsible for the enhanced catalytic properties when compared with pure Au/MCF.